Incidental finding of unilateral partial agenesis of fallopian tube with complete agenesis of ipsilateral ovary during caesarean section with neonatal outcome - Prajapati, Pooja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Congenital unilateral absence of fallopian tube with ipsilateral ovarian agenesis is a rare occurrence with a suggested incidence of 1:11240. Unilateral ovarian agenesis (UOA) and fallopian descent problems are other very rare congenital entity. We presented a case report, detailing one such patient where unilateral partial fallopian tube and ipsilateral ovarian agenesis was seen with neonatal outcome. Our case describes 28 years old G5P2L2A2 un booked case with an obstetric history of 2 spontaneous abortion and two previous full term institutional normal vaginal deliveries (both female child) presented at 37 weeks of gestation with borderline oligo hydramnios (USG suggestive of AFI- 9.1 cm), Posterior placenta, EFW- 2003 g, single loop of cord around fetal neck. On repeat scan USG suggestive of AFI-7.7cm, with discrepancy of >2 weeks between POG and LMP IUGR. Elective caesarean section done after patient and relatives counselling and informed consent done. During C- section unilateral partial agenesis of right fallopian tube and complete agenesis of right ovary found incidentally. The left fallopian tube and ovary was normal. A male baby with birth weight 2.2 kg, well cried was born. USG abdomen of baby was performed to rule out any congenital genitourinary abnormalities. USG revealed, a small aplastic left kidney, for which baby was referred to higher center for further renal function workup. This case was unique since the incidental diagnosis of right ovary and right fallopian tube agenesis occurred during C section instead of imaging.